Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13063564
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Perception: Understanding Stakeholders’ Collaboration in Natural Resources Management through the Evolutionary Theory of Innovation

Abstract: Natural resources management deals with highly complex socioecological systems. This complexity raises a conundrum, since wide-ranging knowledge from different sources and types is needed, but at the same time none of these types of knowledge is able by itself to provide the basis for a viable productive system, and mismatches between the two of them are common. Therefore, a growing body of literature has examined the integration of different types of knowledge in fisheries management. In this paper, we aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…A company's ability for innovation is constrained not just by its boundaries, but also by the cognitive proximity achieved in particular places. Some empirical research has revealed cognitive proximity as the main mechanism for the formation of informal knowledge-circulating networks, and then suggesting that innovation outcomes and inter-organizational learning require the existence of social and cognitive proximity among firms [28][29][30].…”
Section: Cognitive Social Capital and Innovative Performancementioning
confidence: 99%
“…A company's ability for innovation is constrained not just by its boundaries, but also by the cognitive proximity achieved in particular places. Some empirical research has revealed cognitive proximity as the main mechanism for the formation of informal knowledge-circulating networks, and then suggesting that innovation outcomes and inter-organizational learning require the existence of social and cognitive proximity among firms [28][29][30].…”
Section: Cognitive Social Capital and Innovative Performancementioning
confidence: 99%
“…The critical role of the Ogan Ilir Regency in the mining sector must be connected to the importance of mining permits [9]. Mining permits are the legal basis that regulates the region's extraction and exploitation activities of natural resources [10], [11]. With a mining permit, local governments can control and supervise mining activities according to applicable regulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical closeness does not always indicate advantages for the companies in a particular location [7]. Innovation generation and inter-organizational learning seem to require, besides geographical closeness, the presence of cognitive proximity and similar social patterns between geographically adjacent experienced economic actors belonging to a main industry, which allows for successful communication [8]. Thus, industrial agglomeration refers to those organizations located close in geographical terms, and with experience in a main sector, which usually present common cognitive and social features.…”
Section: Introductionmentioning
confidence: 99%